The Effect of Kersen (Muntingia calabura) Fruit Extract Addition to The Yogurt Antibacterial Activity on Escherichia coli: Pengaruh Penambahan Ekstrak Buah Kersen (Muntingia calabura) Terhadap Aktivitas Antibakteri Yogurt Terhadap Escherichia coli - Annisa Krisridwany; Putri Ayu Lestari; Aji Winanta; Sabtanti Harimurti; Vella Lailli Damarwati (Universitas Tadulako, 2023)
Background: Yogurt, completed with lactic acid bacteria, can inhibit the growth of Escherichia coli. The flavonoids, tannin, and saponin of the Muntingia calabura L. plant showed antibacterial activity. Objectives: The present study aims to observe the effect of the addition of Muntingia calabura L. fruit extract to yogurt on the activity of Escherichia coli. Material and Methods: The study was an experimental study with the treatment of addition of Muntingia fruit extract infusion with various concentrations (12.5 %, 25%, 50%, 75%, and 100% with three times replications) to the cow-milk-based yogurt. The staining reagents were used for the phytochemical screening. The mixed muntingia yogurt (MMY) was then centrifuged to obtain supernatant. The antibacterial activity was tested using the disc diffusion method by observing the diameter of the inhibition zone. Plain yogurt was used for the negative control and Cefotaxime for the positive control. Results: In Muntingia fruit extract, flavonoids, tannin, steroid, phenol, and saponin have been observed. The MMY showed antibacterial activity toward E. coli as indicated by the various diameter of inhibition zones of 5.03± 2.66 mm, 4.95± 0.39 mm, 5.68± 0.84 mm, 8.02± 1.45 mm, and 15.73± 1.60 mm for the Muntingia addition concentration of 12.5 %, 25%, 50%, 75%, and 100%, respectively. The diameter of the inhibition zone of negative control was 3.95 mm, while positive control was 45.60 mm. Conclusions: The addition of Muntingia calabura L. fruits extracts to yogurt at concentrations of 75% and 100% could inhibit the growth of E. coli bacteria as categorized for medium and strong inhibitory, respectively.